Еxperimental Review of the Efficiency of the Cultural Compatibility Formation of Future Medical Nurses - Natalia Pedorenko (Pedagogical Discourse, 2019)
Changes in the economic, social, medical and spiritual life of a society contribute  the development of professional aspects of the specialists’ personality.  These requirements are especially relevant for those medical colleges where nurses are trained.  The purpose of the article is to describe the experimental research, analysis and interpretation of its results.Having analyzed the scientific literature, the results of the preliminary stage of the experiment concerning the formation of cultural competence of future nurses, pedagogical conditions were defined: introduction of cultural disciplines into the educational process;  increase of professional competence of teachers of humanitarian disciplines;  development of positive motivation of students through their participation in different types of practice and in non-auditing work;  application of innovative educational technologies with the purpose of teaching to predict possible cultural obstacles in conditions of intercultural professional communication and find ways of their elimination;  the ability to think in a comparative aspect, to evaluate another linguoculture, to understand the features of the representatives of the foreign-language cultural community in professional situations;  consider their country in aspect of crossing cultures and demonstrate cultural tolerance.The examination of the effectiveness of the cultural competence of future nurses, using our created model for forming the cultural competence of future nurses and providing a set of identified pedagogical conditions, was conducted within the framework of a pedagogical experiment, which includes the recording, forming and final stages, aimed at tracking the dynamics of changes of several variables.The examination of students and the testing of the formation of cultural competence before and after the experiment showed that the level of cultural competence of future nurses has increased significantly.  If we analyze the changes that have taken place in the entire sample of participants in the experiment, in all experimental and control groups (EG1, EG2, EG3, EG4, CG), it should be noted that the final test revealed significant differences in the distribution of students by levels of both in separate components and the formation of cultural competence in  general.Key words: future medical nurse, cultural competence, professional qualities, experiment, pedagogical conditions, role of studying, medical college.